Disseminated Acanthamoeba castellanii infection in a patient with AIDS: a case report and literature review - Jiang, Qunqun; Zhang, Zhongwei; Cai, Yuxiang; Chen, Liangjun; Deng, Liping; Xiong, Yong (Frontiers in Medicine, 2024)
Background: Acanthamoeba castellanii infection is a rare condition primarily occurring in immunocompromised patients, with extremely high mortality. There is currently no standard treatment for this condition, and successful treatment reports are scarce.We present a case of Acanthamoeba castellanii infection in a 63-year-old female patient with AIDS, who was admitted to our hospital with symptoms of fever, skin ulcers, subcutaneous nodules, and food regurgitation from the nose while eating. After initial empirical treatment failed, a biopsy of the subcutaneous nodule was performed, and metagenomic next-generation sequencing (mNGS) technology was used to detect pathogenic microorganisms in both the biopsy specimen and blood samples. The results revealed Acanthamoeba castellanii infection.Additionally, histopathological examination of the biopsy specimen and cytological examination of the secretions from the ulcer surface also confirmed this pathogenic infection. The patient's symptoms significantly improved upon discharge after adjusting the treatment regimen to a combination of anti-amebic therapy.Immunocompromised patients presenting with unexplained fever and skin or sinus lesions should be evaluated for Acanthamoeba castellanii infection.Multi-drug combination therapy is required for this organism infection, and a standard treatment protocol still needs further research. Metagenomic next-generation sequencing is a valuable tool for early diagnosis of unknown pathogen infections.